Agrarian transformation in the Near East and North Africa: influences from the work of Lionel Cliffe. (22nd August 2016) - Bush, Ray
ABSTRACT: This article explores the influences of the work of Lionel Cliffe in developing a radical rural political economy. A number of key themes in Cliffe's work are reviewed in order to explore how they have helped to shape a view of rural development that is based, amongst other things, on listening to farmers and exploring why both government policy and often radical interventions fail to deliver the promises of improvements to rural conditions of existence. Case studies from the Near East and North Africa (NENA) highlight absences in policy intervention particularly in the areas of conflict, environmental transformation and economic reform.